Mothers? interactive behaviours and child engagement: The moderating effect of child care - Cruz, Orlanda (2009)
The goal of this study was to investigate the influence of mothers’ interactive behaviours and child care quality on children’s observed sophisticated engagement and non-engagement in child care, after accounting for children’s age and gender and mothers’ education. Specifically, we aimed to study the moderating role of child care quality on the association between mother interactive behaviours and child engagement in child care. We observed 120 mothers and their children (60 boys and 60 girls) aged between 14 and 49 months, attending 15 infant and toddler centres from the Metropolitan area of Porto. Findings indicate that sophisticated engagement is influenced by children’s age, increasing as children get older. Non-engagement (a) is more frequent in boys, (b) decreases as children get older and as mothers’ education increases, and (c) increases as mothers’ active teaching increases and mothers’ responsiveness and child care quality decrease. Results further suggest that child care quality moderates the negative association between mothers’ responsiveness and child’s non-engagement, with a stronger association occurring in lower-quality child care classrooms.DOI: http://dx.doi.org/10.17575/rpsicol.v23i2.329